Weighting Performance Evaluation Criteria Base in Balanced Score Card Approach with Use of Combination Method Shapley value & Bull\'s-eye - Mohammad Hassan Kamfiroozi; Meysam Jafari-Eskandari; Alireza Aliahmadi; Nayyer Ferdosi (مدیریت تولید و عملیات, 2014)
Performance evaluation as a control tool was considered by managers in the organizations and manufactures. In this paper we decide to present a new model for performance evaluation and industrial companies ranking at uncertain conditions. Based on this, we implemented performance evaluation based on balance score card (BSC) method. Beside, we tried to use three parameter interval grey numbers in lieu of linguistic variables. Then evaluation and weighting of fourth indicators is done with use of Bulls-eye-Shapley combination method that is counted as new approach in this article. Reason of utilization of three parameter interval grey numbers and combination method was decreasing of environmental uncertainty on data and model. This combination weighting method can be used as a new method in decision making Science. At final of this paper case study was implemented on industrial companies (nail makers) that ranking of these companies is obtained by use of grey-TOPSIS method (that is a generalization of classic TOPSIS for three parameter interval grey numbers).